ANTI-HYPERCHOLESTEROLEMIC EFFECT OF ETHYL ACETATE EXTRACT FROM STEM BARK OF ARTOCARPUS DASYPHYLLA TOWARD RATTUS NORVEGICUS WISTAR STRAIN - Alfinda Novi Kristanti, Lutfi Nia Kholida, St Khaerunnisa, Nanik Siti Aminah, (SEMIRATA 2015, 2015)
Artocarpus dasyphylla with the local name â€œcempedak utanâ€ is a member of Artocarpus Genus from Moraceae family. It is a rare and endemic plant from east region of Indonesia. The purpose of this study was to determine the antihypercholesterolemic effect of ethyl acetate extract from A. dasyphylla toward the level of total cholesterol, LDL, and HDL of hypercholesterolemic Rattus norvegicus as the prevention effort of atheroschlerosis and CVD. It was due to antioxidant activities of phenolic compounds. The powder of stem bark of Artocarpus dasyphylla was extracted by maceration and partition method. Phenolic total of ethyl acetate extract from stem bark of A. dasyphylla was determined with Folin Ciocalteu reagent, it was 9,86 mg GAE/g of extract. In vivo experiment toward Rattus norvegicus with hypercholesterol diet used randomized post test only control group design. Ethyl acetate extract with the treatment doses 75, 150, 225 mg/kg body weight showed antioxidant activity by decreasing total cholesterol and LDL level to normal level. Paradox result occured to HDL level, the level of HDL decreasing as the increase of dose of sample, but still above the threshold. The best anti-hypercholesterolemic activity was shown by treatment with the dose of ethyl acetate extract from stem bark of A. dasyphylla 150 mg/kg body weight of Rattus norvegicus. Keyword: Artocarpus dasyphylla, antihypercholesterolemic effect, total cholesterol, LDL, HDL, Rattus norvegicus